2014
DOI: 10.1016/j.jcin.2014.01.164
|View full text |Cite
|
Sign up to set email alerts
|

Native Coronary Artery Patency After Coronary Artery Bypass Surgery

Abstract: CTO of surgically bypassed coronary arteries 1 year after coronary artery bypass grafting is extremely common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 28 publications
4
42
2
2
Order By: Relevance
“…2 Second, CABG by itself escalates progression of atherosclerosis or thrombosis in bypassed native coronary arteries 3 ; 43% of bypassed native coronary arteries will develop chronic total occlusions (CTOs) as early as 1 year after CABG. 4 As a result, the prevalence of native artery CTO in patients undergoing coronary angiography reaches 54% in the post-CABG population, higher than in patients without CABG. 5 In summary, when SVGs become diseased or occluded, the whole native coronary tree has sustained substantial changes and has become more difficult to treat.…”
mentioning
confidence: 99%
“…2 Second, CABG by itself escalates progression of atherosclerosis or thrombosis in bypassed native coronary arteries 3 ; 43% of bypassed native coronary arteries will develop chronic total occlusions (CTOs) as early as 1 year after CABG. 4 As a result, the prevalence of native artery CTO in patients undergoing coronary angiography reaches 54% in the post-CABG population, higher than in patients without CABG. 5 In summary, when SVGs become diseased or occluded, the whole native coronary tree has sustained substantial changes and has become more difficult to treat.…”
mentioning
confidence: 99%
“…The presence of a bypass graft is associated with accelerated atherosclerotic disease process and greater risk of development of a CTO of a bypassed vessel. 23) Early studies indicated that patients with occluded bypass grafts were able to recruit the same degree of collaterals as prior to the surgery, 24,25) although other series have suggested that the ability to recruit collaterals to the bypassed vessel is reduced. 26) As we excluded patients who had a previous bypass to the occluded vessel, the presence of a CABG itself appears to negatively impact on the collateral circulations' ability to spontaneously mature.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known in the literature, that the worsening of native bypassed stenosis (until occlusion) on grafted vessels after CABG is a common occurrence. Mainly, it seems to be related to blood flow alterations and shear stress carried out by the grafts themselves, along with cardiovascular risk factors (7,8).…”
mentioning
confidence: 99%